Dynamic network tariffs: Current practices, key issues and challenges. Issue 1 (21st February 2023) - Wang, Kun; Lai, Xinyi; Wen, Fushuan; Singh, Praveen Prakash; Mishra, Sambeet; Palu, Ivo
Abstract: With the ever‐growing demand for electricity, fast development of intermittent renewable energy generation (IREG), and evolving electricity pricing mechanisms, different network tariff schemes are implemented in various countries to address emerging challenges in power system planning and operation as well as electricity market evolution. Given this background, a survey of current practices on dynamic network tariffs in some representative countries is first presented. Subsequently, key issues of dynamic network tariffs including prerequisite, implementation and effects are described. Finally, from the perspective of electricity consumers, distribution system operators (DSOs) and regulatory authorities, the challenges associated with the implementation of dynamic network tariffs are discussed.